Autoestima y Autocuidado en personas adultas mayores que asisten al puesto de salud de Víctor Raúl, 2017 - Solano Villanueva, Iris Giovanna (2018)
SUMMARY The present descriptive - correlational cross - sectional research study has the purpose of determining the relationship between the level of self - esteem and self - care practices in older adults of the Víctor Raúl Town Center, El Porvenir district. This report is based on Dorothea Orem's self-care theory (1998) and the self-esteem framework of Rodríguez, Pellicer and Domínguez (1998). The sample consisted of 47 older adults who met the inclusion criteria mentioned in the research, during the months of November 2016 - February 2017. For the statistical analysis the Gamma statistic was used because both variables are categorical measures in ordinal scale, setting the level of significance at P <0.05, reaching the following conclusions: 74 percent of older adults have a medium level of self-esteem, 17 percent a low level and 9 percent a high level; 77 percent of older adults have regular self-care practices, 19 percent correspond to good self-care practices and 4 percent to poor self-care practices; The relationship between the level of self-esteem and self-care is not significant, as it has a value of p = 0.162.